GIORGIO AGAMBEN: LOS PARADIGMAS SOCIALES Y SUS APORTES A LA FILOSOFÍA DEL DERECHO (2016)
This article analyzes the agambian figures of homo sacer and muslim, state of exception and concentration camp as paradigms to explain the superfluity of contemporary life under a process of degradation and human disintegration which is continuous and increasingly accentuated and perfected. Human life, ethically and politically qualified as just life, is now replaced by the simple life, bare life, biological or vegetative life, stripped of all political, moral, legal attribute. In the meantime the citizen is confused with the homo sacer, Muslim, non-man, whom anyone can kill without committing murder, because life has already been dehumanized by the exclusion, exception and abandon. And the cities become similar to the concentration camps, which rather than places for death, are spaces in which man is transformed into a living-traveling Cadaver, mummy, Muslim by impoverishment, overcrowding, starvation and abandon. This implies that, today, the task of the philosophy of law is not only to consider the best theory of power or justice, but claim and vindicate forms of life understood in all its potentiality, in their ability to live long and specially as potential. Simultaneously with the conception of other philosophical and legal issues relating to contemporary forms of life, we must assume, of course, other theoretical references and also other answers that allow the opening of new horizons of understanding of human life in its relation to law, justice, and community. In this sense, the work of Giorgio Agamben represents a necessary epistemological and methodological framework to understand aw in all its complexity today and address the most pressing problems of our times